ECONOMIC-STATISTICAL ANALYSIS OF THE ROLE OF THE SERVICE INDUSTRY IN THE COUNTRY’S ECONOMY - Oltaev Sh.S (TADQIQOTLAR, 2026)
Abstract: this article presents an economic and statistical analysis of the role of the service sector in the country’s economy, an analysis of entities that create volumes in the service sector and operate in this sector, and an analysis of the dynamics of the development of the service sector in Uzbekistan. The analysis conducted shows, as just one example, that the number of private medical institutions in Uzbekistan is increasing day by day. This, in turn, creates healthy competition in the medical sector, which allows improving the quality of medical services provided to the population and reducing their prices. The above trends are reflected in the fact that new types of services, especially those that are rapidly developing after the Covid-19 pandemic, are entering the Uzbekistan market, which requires special attention when making decisions on economic development strategies, targeted programs and the development of the service sector.